2000
DOI: 10.1016/s0168-3659(99)00257-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of new drug delivery system for protein drugs using silicone (I)

Abstract: A novel technique, by which protein drugs effective in small doses can be released over a long period, was developed using silicone and a water-soluble substance. In this study, interferon (IFN) was used as a model of the protein drugs. The IFN-silicone formulation released IFN over long periods of time in vitro and suppressed tumor growth in nude mice for about 100 days after a single administration. This indicates that physiologically active IFN is released over a prolonged period of time from the IFN-silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…3,4) For example, double-layered formulation IFN/HSA-3 was prepared as follows. An aqueous solution (28.2 g) of IFN (114 MU/ml) was mixed with 2.5 g of gelatin and freeze-dried.…”
Section: Novel Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…3,4) For example, double-layered formulation IFN/HSA-3 was prepared as follows. An aqueous solution (28.2 g) of IFN (114 MU/ml) was mixed with 2.5 g of gelatin and freeze-dried.…”
Section: Novel Drug Deliverymentioning
confidence: 99%
“…Silicone was originally investigated as carrier materials for lipophilic drugs, and several DDS products have been developed. Although silicone had been believed not to be suitable for delivering water-soluble macromolecules, Hsieh et al 1) and Fujioka et al [2][3][4] reported in the 1980s that proteins could be continuously released from silicone. As described above, a number of studies have been conducted on DDS using silicone.…”
mentioning
confidence: 99%
“…However, once HSA is released, VD 3 diffusion is no longer suppressed. On the contrary, since water-filled channels were formed inside the formulation, 9,10) remained VD 3 contacts with water easier than initial phase and the fact accelerates VD 3 release (Fig. 4a).…”
Section: Discussionmentioning
confidence: 99%
“…The excipient-modified silicone elastomer rods were based on implantable matrix and covered-rod formulations described previously in the literature [34][35][36][37][38]. The directly compressed tablets represent the most common and inexpensive drug dosage form, with widespread use for oral administration and occasionally used vaginally.…”
Section: Discussionmentioning
confidence: 99%